Grain separation in a straw walker unit of a combine harvester: Process model. (May 2016) - Myhan, Ryszard; Jachimczyk, Ewelina
Highlights: Mathematical model of grain separation in a straw walker unit was developed. Model takes into account the rheological properties of the straw layer. Kinematic parameters of walkers significantly affect the quality of separation. Model may be used in the design of straw walkers. Model may be used to assist the control straw walkers. Abstract: The key criteria for the assessment of combine harvester are its capacity, and the quality of obtained grain bulk. The simultaneous minimisation of grain losses and the operation time of combine harvester requires, inter alia, the optimal selection of the construction and operating parameters for the straw walker unit, whereas the phenomenon of grain separation and its determinants depending on these parameters are not yet well understood. Therefore, a mathematical model of the process was developed considering: the rheological properties of a straw layer; the phenomena associated with the dynamic strain of the layer, forced by the motion of straw walkers; and the phenomenon of grain separation from a straw-and-grain mixture. The study included natural and simulation experiments. The effects of the following parameters were analysed: the capacity of the straw walker unit; the phase shift angle of the cranks of the straw walker shafts; the angle of inclination of the straw walker sieve surface; the angular velocity; the initial grain content in the mixture. For each combination of parameters under study, the content of separated grain on selected sections of the lengths of walkers was determined. The simulation results indicate that the quality of separation should not be regarded as a simple consequence of the velocity of straw movement over the surface of walkers. The important factors affecting the quality of separation include the kinematic parameters of walkers, dependent not only on the angular velocity, but also on the phase shift angle and the throw of the crank.